The Role of Performance Assessment as a Basis for Compensation in Improving Individual Employee Performance - Yopita S.S, Nova Rosa; Hadi, Samsul; Pulungan, Setyo Budi; Bahri, Syamsul; Haryadi, Budhi; Mulyadi, Edi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
Performance appraisal plays a crucial role in human resource management, particularly in providing an objective basis for appropriate compensation. Fair compensation based on accurate performance appraisals can motivate employees to improve their individual performance, thus positively impacting overall organizational productivity. This study aims to explore the role of performance appraisals in the compensation process and how they can improve individual employee performance. The method used in this study is a qualitative approach with a literature review, where data were collected from various journals, books, and scientific articles related to the topic of performance appraisal and compensation. The results show that clear and transparent performance appraisals not only serve as an evaluation tool for providing compensation, but also serve as a means to identify employee strengths and weaknesses, as well as provide direction for further development. Thus, effective performance appraisals can create a results-oriented work culture and encourage employees to strive harder in achieving organizational goals. This study contributes to the understanding of how compensation based on performance appraisals can be a driving factor for improving individual employee performance.